Empowering Communities: The Role of Zakat in Alleviating Poverty and Promoting Economic Growth in Indonesia - Nasution, Martua; Putra, Dedisyah; Desry Deski (Islamic Circle, 2025)
Poverty remains a major development challenge in Indonesia despite various government programs. In this context, zakat as an Islamic economic instrument holds significant potential to address economic inequality and improve community welfare. However, the optimal utilization of zakat to support economic empowerment and development has yet to be fully realized. This study aims to analyze the role of zakat in alleviating poverty and promoting economic growth in Indonesia, as well as to identify obstacles and strategies for optimizing its management. This research employs a descriptive qualitative approach, utilizing literature review and secondary data analysis from zakat institutions’ reports, academic publications, and national statistics. Additionally, case studies were conducted on economic empowerment programs based on zakat implemented by several prominent zakat institutions in Indonesia. The findings indicate that zakat plays a significant role in increasing the income of zakat recipients (mustahik), expanding access to micro business capital, and encouraging economic self reliance. Productive zakat programs are proven to be more effective in the long term compared to consumptive zakat distribution. Nevertheless, challenges such as low zakat literacy, unequal distribution, and the lack of integration between zakat institutions and government programs remain key barriers. The study recommends enhancing collaboration among institutions, utilizing digital technology for zakat collection and distribution, and strengthening regulations and public education as strategies to maximize zakat's potential in national economic development. Keywords: zakat, economic empowerment, poverty alleviation, Indonesia